Unemployment insurance with response heterogeneity - Conny Wunsch; Véra Zabrodina (University of Basel, Center of Business and Economics (WWZ), 2023)
The generosity of social insurance coverage often increases with the beneficiary's age and their contribution time to social security, but existing policies vary considerably. We study the differentiation of unemployment insurance (UI) generosity by evaluating how the insurance-incentive trade-off varies with age and contribution time. We exploit numerous discontinuities in potential benefit duration in Germany. Contribution time in the last three years carries information on job search efforts, as it is associated with lower moral hazard responses and fiscal externality. We find no significant response heterogeneity in age or longer contribution time horizons. Contrasting these gradients with an approximated insurance value for four UI regimes, we document that steepening the potential benefit duration schedule in contribution time and flattening it in age would have increased welfare.
Keywords: J08; J64; J65; 330; Unemployment insurance; response heterogeneity; policy differentiation